Structural analysis of antigen-specific Ia-bearing regulatory T-cell factors: gel electrophoretic analysis of the antigen-specific augmenting T -cell factor. - Miyatani, S (1983)
An antigen-specific T-cell factor (TaF) that specifically augments the antibody response was purified and biochemically analyzed by NaDodSO4/polyacrylamide gel electrophoresis and isoelectric focusing. Biosynthetically labeled TaF was separated from the Nonidet P-40 extract of T-cell hybridoma FL10, which produces a keyhole limpet hemocyanin-specific TaF, by affinity chromatography either with antigen or with monoclonal anti-I-A antibodies. The material thus obtained was composed of two different types of molecules of molecular weights of 67,000 and 33,000 under nonreducing conditions. After reduction with dithiothreitol, all the molecules migrated to the position of molecular weight 33,000. The absorption studies with immunoadsorbents of antigen and antibodies revealed that the intact TaF is a heterodimer of two discrete polypeptide chains, one carrying a determinant detectable by a monoclonal anti-Tindd directed to an Igh-I -linked allotypic structure of T cells and being associated with the antigen-binding site and the other expressing a unique determinant controlled by the I-A subregion of murine H-2 major histocompatibility complex but being different from known class II polypeptide chains. The antigen-binding polypeptide has an isoelectric point of pH 5.6, and the I-A polypeptide has an isoelectric point of pH 6.3.